CRP Enhances the Innate Killing Mechanisms Phagocytosis and ROS Formation in a Conformation and Complement-Dependent Manner - Zeller, Johannes; Bogner, Balázs; Kiefer, Jurij; Braig, David; Winninger, Oscar; Fricke, Mark; Karasu, Ebru; Peter, Karlheinz; Huber-Lang, Markus; Eisenhardt, Steffen Ulrich (Frontiers in Immunology, 2021)
Phagocytosis and the formation of reactive oxygen species (ROS) in phagocytic leukocytes are an effective killing mechanism of the innate host defense. These cellular processes of innate immunity function in a complex interplay with humoral factors. C-reactive protein (CRP) in its activated, monomeric isoform (mCRP) has been shown to activate immune cells via the classical complement pathway. We investigated the complement-dependent effects of monomeric CRP (mCRP) on neutrophils and monocyte subtypes using complement-specific inhibitors by both flow cytometry and confocal fluorescence microscopy. We demonstrate that CRP-induced ROS generation is a conformation-specific and complement-dependent process in leukocyte subsets with classical monocytes as the primary source of ROS amongst human monocyte subsets. Elucidation of this complex interplay of CRP and complement in inflammation pathophysiology might help to improve anti-inflammatory therapeutic strategies.